Finite Element Analysis of Stress Wave Propagation in Adhesive Joints under Low Speed Impact Tensile Loadings. Issue 1 (21st October 2020) - Xu, Yuqiong; Ke, Yiming; Ma, Xiaoqiang
Abstract: The adhesive joints are suddenly disturbed by the impact loadings in industrial applications. The stress wave propagation and stress distribution in the single lap joint (SLJ) with aluminum alloy adherends and two types of epoxy adhesives under impact tensile loadings are analyzed with the finite element method (FEM) to simulate the drop weight test. The impact velocity is assumed below 2000 mm s −1 and the total impact history is 0.2 ms. The stress is observed throughout the middle plane in the overlap area. The stress wave propagation in the adhesive layer reveal obvious directivity and show the transformation from the elastic wave to the plastic wave. The equivalent Von‐Mises stress increases approximately linearly with the increase of impact energy. At different times, the equivalent Von‐Mises stress along the adhesive longitude present bimodal distribution, while the stress wave propagation characterizes the rising‐falling‐rising trend. The stress singularity area is around 3–5 mm from edges. The equivalent Von‐Mises stress of the transversal middle plane in the adhesive layer is sensitive to rupture with the symmetrical distribution. A damage sensitive area located 2.6 mm away from both edges. The upper interface of the adhesive layer may initiate failure under the low‐velocity impact. Abstract : The stress wave propagation and stress distribution in the single lap joint (SLJ) with aluminum alloy adherends and two types of epoxy adhesives under impact tensile loadings are analyzed with the finite element method to simulate the drop weight test. The impact velocity is assumed 2000 mm s −1 and the total impact history is 0.2 ms.